Comparison of a customized glycemic pellets challenge with the oral sugar test to measure glycemic and insulinemic responses in horses - Kristen Thane; Johanna Sonntag; Tobias Warnken; Dania Reiche; Cassandra Uricchio; Nicholas Frank (Journal of Veterinary Internal Medicine)
Abstract Background Testing for insulin dysregulation (ID) in horses is commonly performed to guide management and therapeutic strategies. Objectives To evaluate a newly developed glycemic pellets challenge (GPC) and compare results to those obtained using the low‐dose oral sugar test (OST). Animals Twenty‐four adult horses with unknown insulin status. Methods A randomized crossover trial was performed. Horses underwent GPC (0.5 g glycemic carbohydrates/kg body weight) and OST (0.15 mL corn syrup/kg body weight) 7 days apart. Feed was withheld before testing and blood samples were collected at T0, T60, T120, and T180 minutes for GPC and at T0, T60, and T90 minutes for OST. Blood glucose concentration was measured using a point‐of‐care glucometer and insulin by radioimmunoassay. Comparisons were made using nonparametric tests, linear regression, and Bland‐Altman agreement analysis. Results Eighteen horses consumed >85% of the GPC pellets within 10 minutes and had acceptable OST results. Maximum glucose (P = .02) and insulin (P = .007) concentrations were significantly higher for GPC compared with OST. Time to maximum insulin concentration (Tmax[ins]) varied within and between tests and neither Tmax[ins] (P = .28) nor maximum insulin concentration (P = .46) was correlated with the time horses took to consume pellets. Conclusions The GPC is well tolerated and may offer another diagnostic testing modality for ID. Blood glucose and insulin concentrations increase during GPC and reach higher concentrations than observed with low‐dose OST. The Tmax[ins] varied for GPC and OST, emphasizing the importance of identifying the optimal time range for the collection of samples to capture diagnostically relevant changes in insulin concentration.